THE RELATIONSHIP OF THE ORGANIZATION CULTURAL PERCEPTION WITH EMPLOYEES PERFORMANCE OF PT AMERICAN INTERNATIONAL ASSURANCE (AIA) - Diah Ayu Retno Savitri; Bagus Wicaksono; Arista Adi Nugroho (Wacana, 2010)
In  Indonesia  today  a  lot  of  insurance   companies   both  foreign  insurance companies or local insurance companies. PT AIA Indonesia is one of the foreign insurance companies the biggest in Indonesia. Things to note is how the corporate culture is taken into account in working. Enterprise organizational culture is the common perception held by the members of corporate organizations. Positive perceptions of organizational culture can provide a significant influence on attitudes and performance. Successful or not efforts in achieving corporate goals or organization is also influenced by the level of employee performance. The purpose of this study is to determine the relationship of the organization cultural perception with employees performance of PT American International Assurance (AIA) Indonesia in Jakarta. Population numbered 408 people. Sample based on characteristics that have determined that between the ages of 30 to 40 years, working time ≥ 5 years and the daily work in the office. Sampling technique with the purposive sampling. Respondents used in this study as many as 60 employees, the research data obtained using a scale of organization cultural perception 49 aitem and scale performance consisting of 51 aitem. Testing research hypotheses using analysis of product-moment correlation is analyzed using SPSS for Windows Version 16.0. Based on the analysis results showed significant positive the relationship of the organization cultural perception with employees performance of PT American International Assurance (AIA) Indonesia, indicated by the value of the correlation coefficient rxy values of 0.634 and p-values in column sig. (2-tailed) 0.000 < 0.05 level of significant (α). Organization culture perceptions of the respondents were classified research, indicated by the empirical average of 96.17 and the hypothetical average of 122.5. Performance on the classified study's respondents, indicated by the empirical average of 118.62 and the hypothetical average of 127.5. Effective role or contribution of organization cultural perception with a performance of 40.2% is indicated by the value of the determinant coefficient (r2) of 0.402. This means that 59.8% there are still other variables that affect the performance of the employees of PT AIA Indonesia, such as leadership style, motivation, personality, and the application of information systems. Keywords: organization cultural perception, performance